2019
DOI: 10.3389/fmicb.2019.01613
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antimicrobial Resistance and Virulence Gene Elements of Salmonella Serovars From Ready-to-Eat (RTE) Shrimps

Abstract: Gastrointestinal illnesses continue to be a global public health risk. Exposure to foodborne Salmonella directly or indirectly through consumption of ready-to-eat seafood can be an important route of infection to humans. This study was designed to estimate the population cell density, prevalence, virulence gene signatures, and antibiotic resistance of Salmonella serovars from ready-to-eat shrimps. Ready-to-eat (RTE) shrimp samples were obtained from different open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 57 publications
11
29
1
Order By: Relevance
“…These results were confirmed by Chen et al [ 37 ] and Duffy et al [ 38 ]. However, the prevalence rates presented by other authors [ 23 , 24 , 30 , 39 ] generally indicate a lower prevalence (0.0–10.0%) of sulfonamide resistance. It is worth noting that strains resistant to older generations of antimicrobials, such as tetracyclines and sulfamethoxazole, are most commonly isolated among Salmonella spp.…”
Section: Discussionmentioning
confidence: 78%
“…These results were confirmed by Chen et al [ 37 ] and Duffy et al [ 38 ]. However, the prevalence rates presented by other authors [ 23 , 24 , 30 , 39 ] generally indicate a lower prevalence (0.0–10.0%) of sulfonamide resistance. It is worth noting that strains resistant to older generations of antimicrobials, such as tetracyclines and sulfamethoxazole, are most commonly isolated among Salmonella spp.…”
Section: Discussionmentioning
confidence: 78%
“…Prevention requires care in all stages of the food chain, from production to consumption (WHO, 2018). Puah et al (2017) found Salmonella enterica in 21.66% (13/60) of retail sashimi samples in Valley Klang, Malaysia, which was also observed by other authors in fresh fish in Nigeria (Beshiru et al, 2019), Jordan (Obdait e Salman, 2017) and Turkey (Onmaz et al, 2015).…”
Section: Resultsmentioning
confidence: 52%
“…It presented intermediate resistance to Cefotaxime, Amikacin, and Tetracycline, and was sensitive to Ampicillin, Cefoxitin, Gentamicin, and Trimethropim-sulfamethoxazole, as shown in Table 3. Recent studies in various countries have reported high resistance profile of fresh fish to these antimicrobial agents, such as fresh shrimp (Penicillin 100%, Ampicillin 83.86%, and Tetracycline 45.45%) in Nigeria (BESHIRU et al, 2019); fresh prawn (Ampicillin 21.9%, Tetracycline 25%, and…”
Section: Antimicrobial Resistance Profilementioning
confidence: 99%
“…In contrast, colistin is mainly used in food-producing animals, but AMR was detected in livestock and humans [218,219]. Multidrug AMR and potentially pathogenic bacteria have been isolated in seafood from different countries [220][221][222][223][224].…”
Section: Residues In Food and Antimicrobial Resistance (Amr)mentioning
confidence: 99%